Identified The Next Alternative CSR Program at PT Pertamina Integrated Terminal Jakarta: Analytic Hierarchy Process Approach - Putu Octavio, I Gusti; Silas Mussry, Jacob (Jurnal Manajemen dan Organisasi, 2024)
This study critically examines the Corporate Social Responsibility (CSR) programs of Pertamina Integrated Terminal Jakarta (ITJ), employing the Analytic Hierarchy Process (AHP) methodology and thematic analysis. The background is to establish an appropriate mechanism for planning CSR programs and demonstrate accountability to internal stakeholders. The study also utilizes an AHP Online System provided by BPMSG to generate objective results. In-depth thematic analysis of interviews reveals a strong integration of CSR into Pertamina ITJ’s business strategy, focusing on community development, sustainability, and stakeholder engagement. The qualitative analysis identifies themes related to the implementation of green buildings in CSR, the importance of program management, evaluation, and continuous improvement. The AHP results indicate that continuous improvement and innovation in CSR programs are prioritized, along with community development and empowerment. Effective management, risk management, and impact measurement are also emphasized, demonstrating the company's commitment to systematic oversight and continuous improvement. The study concludes that Pertamina ITJ's CSR strategy effectively combines systematic management, risk mitigation, and ethical responsibility. While it excels in program management and stakeholder engagement, there are opportunities for enhancement in community development, impact assessment, and sustainability integration.